Research on Auxiliary Diagnosis of Thoracic Fractures Based on Bidirectional Feature Pyramid Network - Li, He; Zhao, Xinyuan (International Journal of Advanced AI Applications, 2025)
Thoracic fractures are a common occurrence in chest injuries, and traditional detection methods are prone to high rates of missed and false detections due to the complexity of thoracic fractures. However, detection methods based on deep learning technology have better detection performance and speed advantages. BiFPN enhances feature expression ability by dynamically adjusting the importance of each layer's features through bidirectional multiple fusion and utilizing a learnable weighting mechanism. This article uses a network model called YOLOv12+BiFPN for thoracic spine fracture detection, replacing the original feature fusion part in YOLOv12+BiFPN with the BiFPN structure. BiFPN allows multiple bidirectional information transfers between feature maps at different levels, improving the recognition ability of fracture areas of different sizes. It adds up-sampling and down-sampling paths to achieve bidirectional feature flow, designs weighted fusion nodes, and uses learnable weights to achieve adaptive feature combination. This module, with its efficient multi-scale feature fusion capability, not only significantly enhances the performance of object detection and classification, but also supports faster training and inference processes, demonstrating outstanding performance in processing large-scale image data. The improvement plan increased the mAP_0.5 index from 0.8612 to 0.9354, and achieved a robust increase of 0.41% to 1.2% in mIoU, while the inference speed only slightly decreased by 3%. The YOLOv12+BiFPN network proposed in this paper greatly improves the accuracy of thoracic fracture detection, significantly promoting the improvement of diagnostic efficiency and precision.